Consistent Organochlorinated Pesticides (OPC) Residues Contamination in Beans Consumed in Gombe Metropolis Nigeria (Journal of Environmental Bioremediation and Toxicology, 2021)
Most of the locally consumed beans in our vicinity contain excess chemicals of pesticides residues which are harmful to humans and environmental hazards to ecosystem. Investigation of this study revealed contamination level of organochlorine pesticides residues in dried beans originating from Nigeria with a view to controlling them, it also studies crude fiber of beans showed that B4 has the highest fiber content, 27.85% and the order of decreasing value as B4, B5 , B1, B3 and B2. The least percentage of crude fiber was shown by B2 in all the beans samples analyzed. This study also investigated the pesticides residue components of the organochlorinated pesticides test. The presence of pesticide residues in all 14 types of organochlorine pesticides in beans is lower than a previously reported level. Despite this, the amount of organochlorine pesticides tested is more than the permitted levels of 0.01 to 0.2 mg/kg, indicating that the beans consumed in the Gombe metropolis included pesticide residues beyond the permissible limit.
Keywords: pesticide residue; dried beans; organochlorine; DDT; Lindane